Community power over conservation regimes: techniques for neutralizing the illegal killing of large carnivores in Finland - Pohja-Mykrä, Mari (Crime, law and social change, 2017)
Certain weaknesses in large carnivore conservation policies have led to a form of political dissent and resistance against dominant conservation regimes, manifested most clearly in the drastic decrease in the Finnish wolf population in 2014. The illegal hunting of large carnivores has been carried out by a particular social group with the support of community members, and hunting violators have been viewed as benefactors by many of their fellow citizens. In the attempt to understand how rural communities sustain alternative ways of regulating their worlds, and how community members negate shame and stigma on behalf of hunting violators, the neutralization techniques presented in the sociological literature by Sykes and Matza provide an effective tool. In collecting the data, we used non-active role playing with empathy-based fictional stories. We obtained a total of 231 narratives from a core group of hunting violators, within which we identified the use of the nine different techniques. These discourses express how a rural identity and way of life is defended and how rural protests against conservation policies are expressed under the pressure of modern conservation regimes. The results address the importance of acknowledging biosecurity issues in wolf territories, of placing a value on local knowledge, and of strengthening trust between the locals and the authorities in implementing responsive and deliberative governance; they also suggest how to formulate effective deterrents to illegal killing and increase compliance with conservation regimes by informal sanctions, based on collective moral judgments and the perceived legitimacy of rules.